Ambulatory Care vs Overnight Hospitalization After Anterior Surgery for Cervical Radiculopathy - Lönnrot, Kimmo; Taimela, Simo; Satopää, Jarno; Saarenpää, Ilkka; Leinonen, Ville; Kivelev, Juri; Silvasti-Lundell, Marja; Förster, Johannes; Pitkänen, Mikko; Raj, Rahul; Kauppinen, Mikko; Westermarck, Riitta; et al. (American Medical Association (AMA), 2025)
IMPORTANCE
During the past decade, spinal surgical procedures have been increasingly performed on an ambulatory basis, a change in clinical practice supported only by observational evidence thus far. There have been no randomized clinical trials (RCTs) comparing ambulatory care with inpatient care after any spinal surgery.
OBJECTIVE
To assess whether ambulatory care is noninferior to overnight hospital surveillance in functional outcome, as measured by Neck Disability Index (NDI), in adults after anterior cervical decompression and fusion (ACDF) for cervical radiculopathy.
DESIGN, SETTING, AND PARTICIPANTS
This parallel group, noninferiority RCT enrolled patients at 3 tertiary neurosurgical centers in Finland (University Hospitals of Helsinki, Turku, and Oulu) between June 2019 and February 2021, with a final follow-up in October 2021. Patients aged 18 to 62 years who underwent 1-level or 2-level ACDF due to cervical radiculopathy were assessed for eligibility. After surgery, participants were randomly assigned to either ambulatory care or overnight hospital surveillance. Intention-to-treat data analyses were conducted in August 2022. I
NTERVENTIONS
Patients randomly assigned to ambulatory care were kept under surveillance for 6 to 8 hours after surgery and then discharged. Patients assigned to overnight hospital surveillance were kept in the ward for 24 hours or longer.
MAIN OUTCOMES AND MEASURES
The primary outcome was NDI at 6 months. A minimal important difference of 17.3 percentage points for NDI was set as the margin of noninferiority. RESULTS Among the 105 patients (mean [SD] age, 47.0 [7.9] years; 54 women [50%]) randomly assigned to ambulatory care (n = 52) or overnight hospital surveillance (n = 53), 94 (90%) completed the trial. Four (8%) patients who received ambulatory care crossed over to overnight hospital surveillance. Seventy-nine patients (75%) had a 1-level ACDF and 26 (25%) had a 2-level ACDF. At 6 months after surgery, the mean NDI was 13.3% (95% CI, 9.3%-17.3%) in the ambulatory care group and 12.2% (95% CI, 8.2%-16.2%) in the overnight hospital surveillance group (betweengroup mean difference, 1.1 [95% CI, −4.6 to 6.8] percentage points).
CONCLUSIONS AND RELEVANCE
In this RCT comparing functional outcomes of ambulatory care vs overnight hospital surveillance after ACDF, ambulatory care resulted in noninferior functional outcomes.